Mathematical problem-solving ability of junior high school students - Rika Aulia Nanda; Usman Usman (International Journal of Trends in Mathematics Education Research, 2022)
Mathematical problem solving is the process of using students' knowledge to find solutions to problems. Students are This study aims to describe the ability of mathematical problem solving in circle content. This research focuses on solving problems based on 4 stages of Polya, namely the ability to solve problems, organize, plan, and check results. This research uses descriptive qualitative method. The research subjects were 6th grade students of SMPN 1 Meureudu as many as 6 people. The selection of subjects was done by purposive sampling with the criteria that students who were recommended by mathematics’ teachers based on the best grades and had participated in at least one Math Olympiad. The research instrument used mathematical problem-solving tests and interviews. Data analysis technique is done by analyzing student work data, interpreting, and concluding. The results of data analysis showed that students' mathematical problem-solving abilities were still low. The low problem-solving ability is seen based on indicators of problem-solving ability that cannot be achieved by most students